ANALYSIS OF ESG DISCLOSURE & CHARACTERISTICS CORPORATE GOVERNANCE ON IDIOSYNCRATIC RISK WITH BUSY BOARD AS A MODERATION VARIABLE YEAR 2015 – 2021 - Windy Bellastrin Agus; Cynthia Afriani Utama (Jurnal Scientia, 2023)
One of the aspect of sustainability lies in the implementation of ESG activities that is done by companies, as well as how they disclose this information to public. Market index that is fluctuative would create a poor information ecosystem and could increase idiosyncratic risk. A good information ecosystem is determined by the characteristic of their corporate governance. There are only little amount of research regarding this subjects. This study aims to analyze the effect of disclosing ESG activities and the characteristics of corporate governance on idiosyncratic risks for public companies in Indonesia. The research used secondary data, consisting of public companies that are listed in IDX website from 2015 – 2021. Idiosyncratic risk is measured using the Fama-French Three Factor Model. ESG disclosure is measured using the ESG score, obtained from the Thomson Reuter website. Using purposive sampling as the sampling method and the analytical method used is multiple regression with panel data. This study found that there was no significant effect of ESG disclosure on idiosyncratic risk. There is a significant negative effect of the size of the Board of Commissioners on idiosyncratic risk and there is a significant negative effect of Gender Diversity on idiosyncratic risk. Then, there is no significant effect of the busy board as a moderating variable on the relationship between ESG Disclosure and idiosyncratic risk. This research could contribute to managers and investors, as well as provide theoretical benefits.